The use of symbolic algebra in learning mathematics: the barrier from formal examination schemes - Berry, John; Fentem, Roger; Partanen, Anna-Maija; Tiihala, Sirkka (NOMAD Nordic Studies in Mathematics Education, 2004)
Using technology in the teaching and learning of mathematics requires, among other things, positive attitudes from students and teachers. In this study, two teachers helped design and then taught two courses of mathematics to four groups of upper secondary school students. Two of the student groups had full access to graphic calculators with symbolic algebra systems and the other two groups had full access to graphing calculators without symbolic algebra software. In this paper we report on the student attitudes and beliefs about using technology in their course within a curriculum that restricts its use in a ’final matriculation examination’. The outcomes suggest that integrated technology teaching impacts in a complex fashion on student attitude. The results of this study suggest that the nature of the assessment system which forms part of the curriculum influences the attitude towards rich usage of the technology.